Electron beam selective melting printing TiAl alloy and Al element loss inhibition method
By optimizing the electron beam selection melting printing process, the problems of Al element loss and mechanical properties in TiAl alloys are solved, and efficient and low-cost TiAl alloy preparation is achieved, with good high-temperature performance and design freedom.
Patent Information
- Application Number
- CN202411236193.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-04
AI Technical Summary
In the process of existing electron beam melt printing of TiAl alloys, there is a large loss of Al elements and difficult to control, resulting in a decrease in mechanical properties, high heat treatment and machining costs and low efficiency.
By optimizing the electron beam selection melting printing process, adjusting the alloy composition and printing parameters, including bottom plate preheating, two-stage method of current and speed, scanning line settings and vacuum control, ensuring that the Al element is evenly distributed and eliminating 'ribbon-like tissue', Improve room temperature and high temperature mechanical properties.
Effective suppression of Al element loss is achieved, the room temperature and high temperature mechanical properties of TiAl alloy are improved, production costs are reduced, process flow is simplified, and production efficiency is improved.
Smart Images

Figure CN119194160A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of engine material design and preparation, in particular to an electron beam selective melting printing TiAl alloy and an Al element loss suppression method. Background Art
[0002] TiAl-based intermetallic alloys have great potential for application in the aerospace industry due to their excellent performance in high-temperature structural applications, including low density, excellent oxidation resistance above 800°C, high strength, and outstanding high-temperature creep properties. Currently, most TiAl alloys are manufactured by conventional casting or powder metallurgy, which have long production cycles, complex shapes, and low design freedom, and usually require additional post-processing processes to achieve customized shapes. Therefore, additive manufacturing provides an alternative method for the rapid manufacture of TiAl alloy parts with high design freedom.
[0003] Electron beam selective melting under vacuum and preheated powder has been proven to be a suitable method for producing TiAl parts. However, the high temperature during printing causes a large amount of Al loss and heterogeneous distribution, which will have an adverse effect on the mechanical properties. TiAl alloys have four typical microstructures: near-γ structure (NG), duplex structure (Duplex), near-lamellar structure (NL) and full-lamellar structure (FL); among them, the heterogeneous distribution caused by Al loss will result in a "banded structure" with a layer of lamellar grains and a layer of equiaxed γ grains. This heterogeneous structure will significantly reduce the strength and plasticity of TiAl alloys.
[0004] Studies have shown that the loss of Al in the electron beam selective melting process is roughly 0.5-2at.%, and Al loss is inevitable, so most existing research focuses on keeping the Al loss ratio consistent. The first reason for Al loss is that when the beam scans the powder during the preheating stage, it will cause the Al element on the powder surface to volatilize; the second reason is that during the melting process, the surface temperature of the molten pool is too high, and the saturated vapor pressure shows that Al is more likely to volatilize. How to overcome these two technical defects is a technical problem that needs to be solved urgently.
[0005] Chinese patent CN116809965A discloses a method for eliminating the lamellar structure of electron beam 3D printed TiAl alloy. The method is to obtain a TiAl alloy ingot with uniform dual-state or near-lamellar structure by heat treatment and unidirectional forging, thereby eliminating the lamellar heterogeneous structure in the original ingot; obviously, this method can only prepare TiAl alloys with simple shapes, and the product obtained by electron beam 3D printing is not the shape and performance of the final product, and cannot fully utilize the direct forming technology advantages of electron beam 3D printing; and the total deformation of the low-carbon steel gasket is 40-45%, the consumption is large, and the production cost is increased.
[0006] Chinese patent CN117753990A discloses a method for eliminating the stratified uneven microstructure of TiAl alloy formed by electron beam selective melting, which is a method for sequentially performing homogenization treatment and high-temperature heat treatment process on the additively manufactured TiAl alloy. By performing segmented heat treatment on the TiAl alloy, the stratified uneven grain band in the direction of forming powder accumulation that is common in the electron beam selective melting TiAl alloy can be effectively eliminated, and it can be adjusted to a near-γ structure and a dual-state structure to obtain an additively manufactured TiAl alloy with fine grains and uniform structure; although heat treatment can improve the stratified uneven microstructure of the alloy, the homogenization treatment is aimed at the product, the processing time is very long, and the heat energy consumed is relatively large, which will lead to grain growth and a decrease in the comprehensive mechanical properties.
[0007] Chinese patent CN116117164A discloses a method for regulating the structure of a TiAl alloy during electron beam selective melting. By adding a heating process at the end of each layer preparation process, the brittle phase in the alloy is reduced, so that the obtained TiAl product has fewer forming defects, a small brittle phase content, and a small phase size and uniform distribution. Although the heating process uses an electron beam, there are many processes and a short time. During the heating process, some organizational structures have no time to change, which is not conducive to the printing of the product. In addition, the scanning speed and current of the electron beam are very large, and the cost is also high.
[0008] Chinese patent CN111485115A discloses a method for controlling the volatilization of Al element by adjusting the vacuum degree of an electron beam cooling hearth furnace, which comprises adding a servo motor, a frequency converter, a controller and a vacuum degree detection device to an existing conventional electron beam cooling hearth furnace, setting the allowable range of vacuum degree, the coarse adjustment step value V, the fine adjustment step value v and the time t on the controller; adopting a power frequency converter and real-time feedback of vacuum degree to realize real-time control of the speed of the vacuum pump driving motor; the method reduces and controls the volatilization by selecting the device structure and process parameters, mainly for controlling the fluctuation of the volatilization rate and the fluctuation of the mechanical properties, rather than for synergistically improving the room temperature performance and high temperature performance of the alloy product. Summary of the invention
[0009] In order to solve the technical problems of "banded structure" stratification phenomenon, difficult to effectively control the volatilization loss of aluminum element, heat treatment and machining for the printed product, complex organization mode, multiple processes, high energy consumption, high cost, low efficiency, etc. in the electron beam melting printing TiAl alloy in the prior art; therefore, the embodiment of the present invention provides an electron beam selective melting printing TiAl alloy and a preparation method that can synergistically improve the room temperature mechanical properties and high temperature mechanical properties (especially) and inhibit the loss of Al element. The technical scheme is as follows:
[0010] An electron beam selective melting and printing TiAl alloy, wherein the electron beam selective melting and printing TiAl alloy for suppressing Al element loss has a height of 15-300 mm, a thickness of 15-50 mm, and a chemical composition in atomic percentage of: Al 40-50 at%, Nb 2-10 at%, Mo 0-0.9 at%, Cr 0-2.5 at%, Si 0-2 at%, C 0-0.5 at%, and the remainder is Ti and unavoidable inclusions; wherein the Al element loss is 0.2-0.35 at%.
[0011] Optionally, the electron beam selective melting printing TiAl alloy is measured on a scale of a molten pool depth, and the difference in Al element content should not be greater than 0.5at.%.
[0012] Optionally, the electron beam selective melting printed TiAl alloy has a multiphase structure, there is no "banded structure" caused by de-Al, and contains 20-30% ordered D0 at room temperature. 19 The microstructure contains Ti3Al phase with ordered B2 structure, β phase with ordered B2 structure with volume fraction ≤10%, and γ phase with L10 structure with volume fraction 60-70%. The number of equiaxed γ grains in the area with 5-10% equiaxed γ grains does not exceed 30% compared with the area with lamellar content of 90-95%.
[0013] Optionally, the difference in strength and plasticity between the forming direction and the horizontal direction of the TiAl alloy printed by electron beam selective melting that suppresses Al element loss is no more than 10%, and the strength and plasticity are respectively increased by 20-50% compared with the heterogeneous distribution caused by Al loss of 1-3at%.
[0014] A method for suppressing Al element loss in electron beam selective melting printing of TiAl alloy according to claim 1, wherein the method for suppressing Al element loss in electron beam selective melting printing of TiAl alloy comprises the following steps:
[0015] S1, smelting: weighing and mixing the TiAl alloy according to the atomic percentage of the electron beam selective melting printing, heating and melting, refining, and casting to obtain an ingot;
[0016] S2. Preparation of alloy powder: The S1 ingot is powdered by a rotating electrode method or gas atomization, and sieved to obtain the alloy powder required for electron beam selective melting and printing of TiAl alloy;
[0017] S3, powder spreading: the alloy powder required for S2 is spread in the electron beam selective melting equipment, and the powder spreading thickness is uniform;
[0018] S4, bottom plate preheating: preheat the bottom plate in the electron beam selective melting equipment, the preheating current adopts a two-stage method, and a grid support is added to the bottom of the sample to reduce the temperature gradient and reduce the tendency of Al loss;
[0019] S5. Printing of TiAl alloy: After the S4 base plate is preheated, the alloy powder is melted and printed to obtain a TiAl alloy of the desired shape, size and precision.
[0020] Optionally, the optimal powder thickness in S3 is close to half of the median powder particle size. At this time, the influence of the molten pool depth and the remelting heating effect is balanced, which is most beneficial to suppressing the loss of Al elements. In production, it is often preferred to use large layer thickness for printing. At this time, it is necessary to more finely control the melting depth and defocus value.
[0021] Optionally, the mesh number of the sieving in S2 is 350 mesh, and the thickness of the powder spread in S3 is 40-120 μm.
[0022] Optionally, in S4, the preheating temperature of the bottom plate is 900-950°C, and the sintering temperature of the powder under the bottom plate is 850-900°C; in the two-stage method, the first stage method uses a smaller current, and gradually increases from 10mA to 40mA using an automatic interpolation method for 5-10 times; the second stage method uses a large current, and gradually increases from 40mA to 60mA using an automatic interpolation method for 5-10 times.
[0023] Optionally, the electron beam scanning lines preheated in S4 are vertical lines that run through the entire preheating format, rotate 90° after each scan, the number of preheating scanning lines is 10-16, and the scanning line spacing is 0.2-1 mm.
[0024] Optionally, in S4, the vacuum degree of the printing chamber is maintained at at least 10 -2 mbar, after evacuating, fill with a small amount of argon and high-purity argon gas, and cycle two to three times.
[0025] Optionally, within 10 ms after the base plate is preheated in S4, the melting beam should be output to perform melting and printing of the alloy powder; the melting and printing process of S5 includes the following steps:
[0026] S51, return time setting: when dividing and slicing the model, the return time of the scan line is set to a fixed value. If a single line is too long, it is re-divided into a combination of several short lines;
[0027] S52, current-speed selection: complete the return time setting in S51, and melt the powder. The melting parameters of different types of powders can be determined by orthogonal test. The following parameters are applicable to TiAl alloy powder: when the powder layer thickness is 40-70μm, the scanning speed is 1.8-2.8m / s, the scanning current is 3-6mA, the line spacing is 0.05-0.2mm, and the defocus value is 20-30mA; when the powder layer thickness is 70-120μm, the scanning speed is 2.0-4.8m / s, the scanning current is 4-9mA, the line spacing is 0.05-0.2mm, and the defocus value is 30-60mA;
[0028] S53, scan line setting: In S52, the melting scan line is spliced by short lines, and rotated 90° after each layer is scanned. In the case of a serious tendency of powder blowing, the dehoff strategy or random strategy can be used instead.
[0029] Optionally, the microstructure of the TiAl alloy of the required shape, size and precision in S5 is analyzed by the energy spectrum of a scanning electron microscope. The Al element in the energy spectrum surface scanning diagram is evenly distributed in each layer, and there is no obvious contrast difference in the forming direction and the horizontal direction; using X-ray diffraction analysis, D0 19 The difference in the contents of Ti3Al phase in the B2 structure, β phase in the L10 structure and γ phase in the L10 structure measured by the half-width method should not be greater than 5%.
[0030] Optionally, the temperature difference between the top and bottom of the molten pool of any printing parameter combination of the TiAl alloy of the required shape, size and accuracy in S5 is no more than 1500°C, and the temperature of the top of the molten pool does not exceed 2500°C.
[0031] Optionally, after S5, in the powder recovery stage, the powders that have turned into gray-black and bright white colors should be removed. These powders are generally caused by de-Al or Al plating.
[0032] Technical principle of the present invention:
[0033] Print out TiAl alloy without stratification, with the difference of Al element distribution between the upper and lower molten pool not more than 0.5at.%, and the difference of strength and plasticity between the forming direction and the horizontal direction not more than 10%. This method reduces the temperature difference between the powder and the molten pool, and obtains a fine full-lamellar structure with uniform elements and grains. This structure has good high-temperature performance and proposes a new concept for blade materials and processing.
[0034] Compared with the prior art, the above technical solution has at least the following beneficial effects:
[0035] The above scheme, the present invention proposes a method for electron beam selective melting printing of TiAl alloy and Al element loss suppression, which can solve many technical problems existing in the existing electron beam printing process of TiAl alloy, thereby reducing production costs and improving economic benefits.
[0036] The present invention optimizes the phase change path and the temperature range of the single-phase region of the alloy through reasonable composition adjustment, and effectively controls the loss of Al element in the printing process by controlling factors such as base plate preheating, current and speed, scanning line setting in the preheating stage and return time, current and speed, scanning line setting in the melting stage.
[0037] The present invention obtains a higher printing process window through the optimization design of printing parameters, which is beneficial to controlling the loss process of Al element during the printing process; a TiAl alloy with no stratification and the difference in Al element distribution between the upper and lower parts of the molten pool is not more than 0.5at.%, and the difference in strength and plasticity between the forming direction and the horizontal direction is not more than 10% is printed.
[0038] The preparation method of the present invention completely eliminates the "banded structure" stratification phenomenon in TiAl alloy through parameter optimization design, can reduce the temperature difference between powder and molten pool, and obtain fine full-lamellar structure with uniform elements and grains. This structure has good high-temperature performance and proposes a new concept for blade materials and processing.
[0039] The preparation method of the present invention can be widely used for printing TiAl alloys such as TNM, 4822, high Nb-TiAl, 45XD, etc., and can achieve the suppression of aluminum element loss, and has strong alloy process adaptability; in particular, the design parameter domain in the preparation method is controllable, and there is no need to add additional equipment or links. The process is simple, the cycle is short, the cost is low, and the efficiency is high.
[0040] In summary, compared with other traditional methods, the method of the present invention can print TiAl alloy products with high shape design freedom and high dimensional accuracy by selecting components and controlling the preheating stage and the melting stage; it can synergistically improve the room temperature and high temperature mechanical properties, inhibit the loss of Al elements, has high resource utilization, short process, high efficiency, and is conducive to large-scale industrial production and promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0042] Figure 1 This is a SEM-BSE image of the TiAl alloy printed by electron beam selective melting in Comparative Example 1 of the present invention;
[0043] Figure 2 This is a SEM-BSE image of TiAl alloy printed by electron beam selective melting using the Al element loss suppression method in Example 1 of the present invention;
[0044] Figure 3 This is a SEM-BSE image of the TiAl alloy printed by electron beam selective melting in comparative example 2 of the present invention;
[0045] Figure 4 This is a SEM-BSE image of TiAl alloy printed by electron beam selective melting using the Al element loss suppression method in Example 2 of the present invention;
[0046] Figure 5 This is a SEM-BSE image of the TiAl alloy printed by electron beam selective melting in comparative example 3 of the present invention;
[0047] Figure 6 This is a SEM-BSE image of TiAl alloy printed by electron beam selective melting using the Al element loss suppression method in Example 3 of the present invention;
[0048] Figure 7 This is a SEM-BSE image of the TiAl alloy printed by electron beam selective melting in comparative example 4 of the present invention;
[0049] Figure 8 This is a SEM-BSE image of TiAl alloy printed by electron beam selective melting using the Al element loss suppression method in Example 4 of the present invention;
[0050] Fig. 9 This is a SEM-EDX image of a TiAl alloy printed by electron beam selective melting using an Al element loss suppression method in Example 5 of the present invention;
[0051] Fig.10 This is a SEM-EDX image of a TiAl alloy printed by electron beam selective melting using an Al element loss suppression method in Example 6 of the present invention;
[0052] Fig.11 In Example 5 of the present invention, the detection area of TiAl alloy printed by electron beam selective melting through the Al element loss suppression method is about 25mm 2 Ingredient content diagram;
[0053] Fig.12 In Example 6 of the present invention, the detection area of TiAl alloy printed by electron beam selective melting through the Al element loss suppression method is about 25mm 2 Ingredient content diagram;
[0054] Fig.13In Example 7 of the present invention, the detection area of TiAl alloy printed by electron beam selective melting through the Al element loss suppression method is about 25mm 2 Ingredient content diagram;
[0055] Fig.14 This is a 12-point composition detection table of TiAl alloy printed by electron beam selective melting using the Al element loss suppression method in Example 7 of the present invention. DETAILED DESCRIPTION
[0056] The technical solution of the present invention is described below in conjunction with the accompanying drawings.
[0057] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to indicate examples, illustrations or explanations. Any embodiment or design described as "example" in the present invention should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of the word "example" is intended to present the concept in a specific way. In addition, in the embodiments of the present invention, the meaning expressed by "and / or" can be both, or it can be either of the two.
[0058] In the embodiments of the present invention, "image" and "picture" can sometimes be used interchangeably. It should be noted that when the difference between them is not emphasized, the meanings they want to express are the same. "of", "corresponding" and "corresponding" can sometimes be used interchangeably. It should be noted that when the difference between them is not emphasized, the meanings they want to express are the same.
[0059] In the embodiments of the present invention, sometimes a subscript such as W1 may be written as a non-subscript such as W1. When the difference is not emphasized, the meanings to be expressed are the same.
[0060] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0061] An electron beam selective melting and printing TiAl alloy, wherein the electron beam selective melting and printing TiAl alloy for suppressing Al element loss has a height of 15-300 mm, a thickness of 15-50 mm, and a chemical composition in atomic percentage of: Al 40-50 at%, Nb 2-10 at%, Mo 0-0.9 at%, Cr 0-2.5 at%, Si 0-2 at%, C 0-0.5 at%, and the remainder is Ti and unavoidable inclusions; wherein the Al element loss is 0.2-0.35 at%.
[0062] In particular, when the electron beam selective melting printing TiAl alloy is measured on a scale of a molten pool depth, the difference in Al element content should not be greater than 0.5 at.%.
[0063] In particular, the electron beam selective melting printed TiAl alloy has a multiphase structure, does not have a "banded structure" caused by de-Al, and contains 20-30% ordered D0 at room temperature. 19 The microstructure contains Ti3Al phase with ordered B2 structure, β phase with ordered B2 structure with volume fraction ≤10%, and γ phase with L10 structure with volume fraction 60-70%. The number of equiaxed γ grains in the area with 5-10% equiaxed γ grains does not exceed 30% compared with the area with lamellar content of 90-95%.
[0064] In particular, the difference in strength and plasticity between the forming direction and the horizontal direction of the electron beam selective melting printed TiAl alloy that suppresses Al element loss is no more than 10%, and the strength and plasticity are respectively increased by 20-50% compared with the heterogeneous distribution caused by Al loss of 1-3at%.
[0065] A method for suppressing Al element loss in electron beam selective melting printing of TiAl alloy according to claim 1, wherein the method for suppressing Al element loss in electron beam selective melting printing of TiAl alloy comprises the following steps:
[0066] S1, smelting: weighing and mixing the TiAl alloy according to the atomic percentage of the electron beam selective melting printing, heating and melting, refining, and casting to obtain an ingot;
[0067] S2. Preparation of alloy powder: The S1 ingot is powdered by a rotating electrode method or gas atomization, and sieved to obtain the alloy powder required for electron beam selective melting and printing of TiAl alloy;
[0068] S3, powder spreading: the alloy powder required for S2 is spread in the electron beam selective melting equipment, and the powder spreading thickness is uniform;
[0069] S4, bottom plate preheating: preheat the bottom plate in the electron beam selective melting equipment, the preheating current adopts a two-stage method, and a grid support is added to the bottom of the sample to reduce the temperature gradient and reduce the tendency of Al loss;
[0070] S5. Printing of TiAl alloy: After the S4 base plate is preheated, the alloy powder is melted and printed to obtain a TiAl alloy of the desired shape, size and precision.
[0071] In particular, the optimal powder thickness in S3 is close to half of the median powder particle size. At this time, the influence of the molten pool depth and the remelting heating effect is balanced, which is most beneficial to suppressing the loss of Al elements. In production, it is often preferred to use large layer thickness for printing. At this time, more precise control of the melting depth and defocus value is required.
[0072] In particular, the mesh number of the sieve in S2 is 350 mesh, and the thickness of the powder in S3 is 40-120 μm.
[0073] In particular, the preheating temperature of the bottom plate in S4 is 900-950℃, and the sintering temperature of the powder under the bottom plate is 850-900℃; in the two-stage method, the first stage method uses a smaller current, gradually increasing from 10mA to 40mA using the automatic interpolation method for 5-10 times; the second stage method uses a large current, gradually increasing from 40mA to 60mA using the automatic interpolation method for 5-10 times.
[0074] In particular, the electron beam scanning line for preheating in S4 adopts a vertical line that runs through the entire preheating format, rotates 90° after each scan, the number of branch lines of the preheating scanning line is 10-16, and the scanning line spacing is 0.2-1mm.
[0075] In particular, the vacuum level of the printing chamber in S4 is maintained at at least 10 -2 mbar, after evacuating, fill with a small amount of argon and high-purity argon gas, and cycle two to three times.
[0076] In particular, in S4, the melting beam should be output within 10ms after the base plate is preheated to perform melting and printing of the alloy powder; the melting and printing process of S5 includes the following steps:
[0077] S51, return time setting: when dividing and slicing the model, the return time of the scan line is set to a fixed value. If a single line is too long, it is re-divided into a combination of several short lines;
[0078] S52, current-speed selection: complete the return time setting in S51, and melt the powder. The melting parameters of different types of powders can be determined by orthogonal test. The following parameters are applicable to TiAl alloy powder: when the powder layer thickness is 40-70μm, the scanning speed is 1.8-2.8m / s, the scanning current is 3-6mA, the line spacing is 0.05-0.2mm, and the defocus value is 20-30mA; when the powder layer thickness is 70-120μm, the scanning speed is 2.0-4.8m / s, the scanning current is 4-9mA, the line spacing is 0.05-0.2mm, and the defocus value is 30-60mA;
[0079] S53, scan line setting: In S52, the melting scan line is spliced by short lines, and rotated 90° after each layer is scanned. In the case of a serious tendency of powder blowing, the dehoff strategy or random strategy can be used instead.
[0080] In particular, the microstructure of the TiAl alloy with the required shape, size and precision in S5 was analyzed by energy spectrum analysis of a scanning electron microscope. The Al element in the energy spectrum scanning diagram was evenly distributed in each layer, and there was no obvious contrast difference in the forming direction and the horizontal direction. Using X-ray diffraction analysis, D0 19The difference in the contents of Ti3Al phase in the B2 structure, β phase in the L10 structure and γ phase in the L10 structure measured by the half-width method should not be greater than 5%.
[0081] In particular, the temperature difference between the top and bottom of the molten pool for any combination of printing parameters of the TiAl alloy with the required shape, size and accuracy in S5 is no more than 1500°C, and the temperature of the top of the molten pool does not exceed 2500°C.
[0082] In particular, powders that have turned gray-black and bright white should be removed during the powder recovery stage after S5. These powders are generally caused by de-Al or Al plating.
[0083] Example 1
[0084] In this embodiment, the electron beam selective melting and printing TiAl alloy is performed by the Al element loss suppression method. The height is 15 mm, the thickness is 15 mm, and the chemical composition is calculated by atomic percentage: Al 45at%, Nb 8at%, and the remainder is Ti and unavoidable inclusions; wherein, the Al element loss is 0.2at%.
[0085] A method for suppressing Al element loss in the electron beam selective melting printing TiAl alloy to be prepared in this embodiment includes the following steps:
[0086] S1, smelting: weighing and mixing the TiAl alloy according to the atomic percentage of the electron beam selective melting printing, heating and melting, refining, and casting to obtain an ingot;
[0087] S2. Preparation of alloy powder: The S1 ingot is powdered by a rotating electrode method (PREP), and sieved to a mesh size of 350 to obtain the alloy powder required for electron beam selective melting and printing of TiAl alloy;
[0088] S3, powder spreading: the alloy powder required for S2 is spread in the electron beam selective melting equipment, the powder spreading thickness is 50μm, and the powder spreading thickness is uniform;
[0089] S4, base plate preheating: preheat the base plate in the electron beam selective melting equipment, and keep the vacuum degree of the printing chamber at least 10 -2 mbar, after vacuuming, a small amount of high-purity argon gas is filled in, and the cycle is two to three times; the preheating temperature of the bottom plate is 920℃, and the sintering temperature of the powder under the bottom plate is 850℃; the preheating current adopts a two-stage method. In the two-stage method, a smaller current is used in the first stage method, and the current is gradually increased from 18mA to 38mA in 10 times using the automatic interpolation method; the second stage method adopts a large current, and the current is gradually increased from 40mA to 58mA in 10 times using the automatic interpolation method; a grid support is added to the bottom of the sample to reduce the temperature gradient and reduce the tendency of Al loss;
[0090] The preheating electron beam scanning line adopts a vertical line that runs through the entire preheating format, and rotates 90° after each scan. The number of preheating scanning lines is 10, and the scanning line spacing is 1mm.
[0091] S5, TiAl alloy printing: within 10ms after the base plate is preheated in S5, the melting beam should be output to melt and print the alloy powder to obtain the TiAl alloy of the required shape, size and accuracy; the melting printing process includes the following steps:
[0092] S51, return time setting: when dividing and slicing the model, the return time of the scan line is set to a fixed value. If a single line is too long, it is re-divided into a combination of several short lines;
[0093] S52, current-speed selection: complete the return time setting in S51, and melt the powder. The melting parameters of different types of powders can be determined by orthogonal test. The following parameters are applicable to TiAl alloy powder: scanning speed is 2.6m / s, scanning current is 5mA, line spacing is 0.08mm, and defocus value is 30mA;
[0094] S53, scan line setting: In S52, the melting scan line is spliced by short lines, and rotated 90° after each layer is scanned. In the case of a serious tendency of powder blowing, the dehoff strategy or random strategy can be used instead.
[0095] The microstructure of the TiAl alloy of the desired shape, size and precision in Example S5 was analyzed by scanning electron microscope (SEM-BSE). Figure 2 As shown in the figure, the composition contrast of the molten pool is the same as that of the surrounding area, and the "layering" feature has been completely eliminated; the Al element is evenly distributed in each layer, and there is no obvious contrast difference in the forming direction and the horizontal direction; using X-ray diffraction analysis, D0 19 The values of the Ti3Al phase of the B2 structure, the β phase of the L10 structure and the γ phase of the L10 structure measured by the half-width method have a maximum difference of 3%.
[0096] In the present embodiment S5, the temperature difference between the top and bottom of the molten pool for any combination of printing parameters of the TiAl alloy of the required shape, size and precision is 1000°C, and the temperature of the top of the molten pool is 2200°C.
[0097] In this embodiment, after S5, in the powder recovery stage, the powders that have turned into gray-black and bright white colors should be removed. These powders are generally caused by de-Al or Al plating.
[0098] The TiAl alloy prepared by electron beam selective melting printing in this embodiment is measured on the scale of a molten pool depth, and the maximum difference in Al element content is 1 at.%.
[0099] The TiAl alloy prepared by electron beam selective melting printing in this embodiment has a multiphase structure, does not have a "banded structure" caused by de-Al, and contains 20% ordered D0 at room temperature. 19 The microstructure consists of a Ti3Al phase with a structure, a β phase with an ordered B2 structure at a volume fraction of 10%, and a γ phase with an L10 structure at a volume fraction of 70%. In the microstructure, the number of equiaxed γ grains in the area with 5% equiaxed γ grains does not exceed 30% compared with the area with 95% lamellar content.
[0100] The maximum difference in strength and plasticity between the forming direction and the horizontal direction of the electron beam selective melting printed TiAl alloy to be prepared in this embodiment is 5%, and the strength and plasticity are increased by 20% and 50% respectively compared with the heterogeneous distribution caused by 1.5at% Al loss.
[0101] The room temperature properties of the electron beam selective melting printing TiAl alloy to be prepared in this embodiment in the forming direction are as follows: tensile strength is 950 MPa, yield strength is 800 MPa, and elongation is 1.5%.
[0102] Comparative Example 1
[0103] The thickness and composition of the electron beam selective melting printing TiAl alloy to be prepared in this comparative example are the same as those in Example 1. The preparation method comprises the following steps:
[0104] Steps S1-S3 are the same as those in Example 1;
[0105] S4, bottom plate preheating: preheat the bottom plate in the electron beam selective melting equipment, the preheating temperature of the bottom plate is 1000℃, and the sintering temperature of the powder under the bottom plate is 980℃; the preheating current is 26-44mA and scanned 30 times; no grid support is added to the bottom of the sample;
[0106] Among them, the preheating electron beam scanning line adopts a vertical line that runs through the entire preheating format and rotates 90° after each scan;
[0107] S5, printing of TiAl alloy: After the preheating of the bottom plate in S5 is completed, the melting beam is output to perform melting printing of the alloy powder to obtain the TiAl alloy of the required shape, size and accuracy; during the melting printing process, the melting scanning speed is 2.0m / s, the scanning current is 8mA, and the line spacing is 0.1mm.
[0108] The microstructure of the TiAl alloy of the desired shape, size and precision in this comparative example S5 was analyzed by scanning electron microscope energy spectrum analysis. The microstructure SEM-BSE is as follows: Figure 1 As shown in the figure, there is a clear difference in composition contrast between the molten pool and its surroundings, with a significant "layered" feature.
[0109] In this comparative example S5, the temperature difference between the top and bottom of the molten pool for any combination of printing parameters of the TiAl alloy of the desired shape, size and precision is 1900°C, and the temperature of the top of the molten pool is 3100°C.
[0110] The electron beam selective melting printing TiAl alloy to be prepared in this comparative example was measured on a molten pool depth scale, and the minimum difference in Al element content was 2.6 at.%.
[0111] The difference in strength and plasticity between the forming direction and the horizontal direction of the electron beam selective melting printing TiAl alloy to be prepared in this comparative example is at least 20%.
[0112] The room temperature properties of the electron beam selective melting printing TiAl alloy in the forming direction to suppress the loss of Al element prepared in this comparative example are as follows: tensile strength of 550 MPa, yield strength of 500 MPa, and elongation of 0.5%.
[0113] Example 2
[0114] In this embodiment, the height of the TiAl alloy printed by electron beam selective melting through the Al element loss suppression method is 35 mm, the thickness is 15 mm, and the chemical composition is calculated by atomic percentage: Al 48at%, Cr 2at%, Nb 2at%, and the remainder is Ti and unavoidable inclusions; wherein, the Al element loss is 0.22at%.
[0115] A method for suppressing Al element loss in the electron beam selective melting printing TiAl alloy to be prepared in this embodiment includes the following steps:
[0116] S1, smelting: weighing and mixing the TiAl alloy according to the atomic percentage of the electron beam selective melting printing, heating and melting, refining, and casting to obtain an ingot;
[0117] S2. Preparation of alloy powder: The S1 ingot is powdered by a rotating electrode method (PREP), and sieved to a mesh size of 350 to obtain the alloy powder required for electron beam selective melting and printing of TiAl alloy;
[0118] S3, powder spreading: the alloy powder required for S2 is spread in the electron beam selective melting equipment, the powder spreading thickness is 50μm, and the powder spreading thickness is uniform;
[0119] S4, base plate preheating: preheat the base plate in the electron beam selective melting equipment, and keep the vacuum degree of the printing chamber at least 10 -2mbar, after vacuuming, a small amount of high-purity argon gas is filled in, and the cycle is two to three times; the preheating temperature of the bottom plate is 920℃, and the sintering temperature of the powder under the bottom plate is 880℃; the preheating current adopts a two-stage method. In the two-stage method, a smaller current is used in the first stage method, and the current is gradually increased from 16mA to 40mA in 10 times using the automatic interpolation method; the second stage method adopts a large current, and the current is gradually increased from 40mA to 60mA in 8 times using the automatic interpolation method; a grid support is added to the bottom of the sample to reduce the temperature gradient and reduce the tendency of Al loss;
[0120] The preheating electron beam scanning line adopts a vertical line that runs through the entire preheating format, and rotates 90° after each scan. The number of preheating scanning lines is 12, and the scanning line spacing is 1mm.
[0121] S5, TiAl alloy printing: within 10ms after the base plate is preheated in S5, the melting beam should be output to melt and print the alloy powder to obtain the TiAl alloy of the required shape, size and accuracy; the melting printing process includes the following steps:
[0122] S51, return time setting: when dividing and slicing the model, the return time of the scan line is set to a fixed value. If a single line is too long, it is re-divided into a combination of several short lines;
[0123] S52, current-speed selection: complete the return time setting in S51, and melt the powder. The melting parameters of different types of powders can be determined by orthogonal test. The following parameters are applicable to TiAl alloy powder: scanning speed is 2.6m / s, scanning current is 5mA, line spacing is 0.08mm, and defocus value is 35mA;
[0124] S53, scan line setting: In S52, the melting scan line is spliced by short lines, and rotated 90° after each layer is scanned. In the case of a serious tendency of powder blowing, the dehoff strategy or random strategy can be used instead.
[0125] The microstructure of the TiAl alloy of the desired shape, size and precision in Example S5 was analyzed by scanning electron microscope (SEM-BSE). Figure 4 As shown in the figure, the composition contrast of the molten pool is the same as that of the surrounding area, and the "layering" feature has been completely eliminated; the Al element is evenly distributed in each layer, and there is no obvious contrast difference in the forming direction and the horizontal direction; using X-ray diffraction analysis, D0 19 The values of the Ti3Al phase of the B2 structure, the β phase of the L10 structure and the γ phase of the L10 structure measured by the half-width method have a maximum difference of 3%.
[0126] In the present embodiment S5, the temperature difference between the top and bottom of the molten pool for any combination of printing parameters of the TiAl alloy of the required shape, size and precision is 800°C, and the temperature of the top of the molten pool is 2000°C.
[0127] In this embodiment, after S5, in the powder recovery stage, the powders that have turned into gray-black and bright white colors should be removed. These powders are generally caused by de-Al or Al plating.
[0128] The TiAl alloy prepared by electron beam selective melting printing in this embodiment is measured on the scale of a molten pool depth, and the maximum difference in Al element content is 0.4at.%.
[0129] The TiAl alloy prepared by electron beam selective melting printing in this embodiment has a multiphase structure, does not have a "banded structure" caused by de-Al, and contains 25% ordered D0 at room temperature. 19 The microstructure contains 6% Ti3Al phase with ordered B2 structure, 6% β phase with ordered B2 structure and 69% γ phase with L10 structure; the number of equiaxed γ grains in the area with 6% equiaxed γ grains is as large as 20% compared with the area with 94% lamellar content.
[0130] The maximum difference in strength and plasticity between the forming direction and the horizontal direction of the electron beam selective melting printed TiAl alloy to be prepared in this embodiment is 7%, and the strength and plasticity are increased by 40% and 50% respectively compared with the heterogeneous distribution caused by the loss of 2.8at% of Al.
[0131] The room temperature properties of the electron beam selective melting printing TiAl alloy to be prepared in this embodiment in the forming direction are: tensile strength of 800 MPa, yield strength of 700 MPa, and elongation of 1.2%.
[0132] Comparative Example 2
[0133] The thickness and composition of the electron beam selective melting printing TiAl alloy to be prepared in this comparative example are the same as those in Example 2. The preparation method comprises the following steps:
[0134] Steps S1-S3 are the same as those in Example 1;
[0135] S4, bottom plate preheating: preheat the bottom plate in the electron beam selective melting equipment, the preheating temperature of the bottom plate is 980℃, and the powder sintering temperature under the bottom plate is 900℃; the preheating current is 28-45mA and scanned 26 times; no grid support is added to the bottom of the sample;
[0136] Among them, the preheating electron beam scanning line adopts a vertical line that runs through the entire preheating format and rotates 90° after each scan;
[0137] S5, printing of TiAl alloy: After the preheating of the bottom plate in S5 is completed, the melting beam is output to perform melting printing of the alloy powder to obtain the TiAl alloy of the required shape, size and accuracy; during the melting printing process, the melting scanning speed is 1.6m / s, the scanning current is 8.2mA, and the line spacing is 0.12mm.
[0138] The microstructure of the TiAl alloy of the desired shape, size and precision in this comparative example S5 was analyzed by scanning electron microscope energy spectrum analysis. The microstructure SEM-BSE is as follows: Figure 3 As shown in the figure, there is a clear difference in composition contrast between the molten pool and its surroundings, with a significant "layered" feature.
[0139] In this comparative example S5, the temperature difference between the top and bottom of the molten pool for any combination of printing parameters of the TiAl alloy of the desired shape, size and precision is 1800°C, and the temperature of the top of the molten pool is 2700°C.
[0140] The TiAl alloy prepared by electron beam selective melting printing in this comparative example was measured on the scale of a molten pool depth, and the difference in Al element content was as small as 2.5 at.%.
[0141] The difference in strength and plasticity between the forming direction and the horizontal direction of the electron beam selective melting printing TiAl alloy to be prepared in this comparative example is at least 46%.
[0142] The room temperature properties of the electron beam selective melting printing TiAl alloy in the forming direction to be prepared in this comparative example and to suppress the loss of Al element are as follows: tensile strength is 630 MPa, yield strength is 570 MPa, and elongation is 0.3%.
[0143] Example 3
[0144] In this embodiment, the height of the TiAl alloy printed by electron beam selective melting through the Al element loss suppression method is 75 mm, the thickness is 15 mm, and the chemical composition is calculated by atomic percentage: Al 44.5at%, Nb 4at%, Mo 0.5at%, and the remainder is Ti and unavoidable inclusions; wherein, the Al element loss is 0.32at%.
[0145] A method for suppressing Al element loss in the electron beam selective melting printing TiAl alloy to be prepared in this embodiment includes the following steps:
[0146] S1, smelting: weighing and mixing the TiAl alloy according to the atomic percentage of the electron beam selective melting printing, heating and melting, refining, and casting to obtain an ingot;
[0147] S2. Preparation of alloy powder: The S1 ingot is powdered by a rotating electrode method (PREP), and sieved to a mesh size of 350 to obtain the alloy powder required for electron beam selective melting and printing of TiAl alloy;
[0148] S3, powder spreading: the alloy powder required for S2 is spread in the electron beam selective melting equipment, the powder spreading thickness is 70μm, and the powder spreading thickness is uniform;
[0149] S4, base plate preheating: preheat the base plate in the electron beam selective melting equipment, and keep the vacuum degree of the printing chamber at least 10 -2 mbar, after vacuuming, a small amount of high-purity argon gas is filled in, and the cycle is two to three times; the preheating temperature of the bottom plate is 920℃, and the sintering temperature of the powder under the bottom plate is 870℃; the preheating current adopts a two-stage method. In the two-stage method, a smaller current is used in the first stage method, and the current is gradually increased from 16mA to 36mA in 10 times using the automatic interpolation method; the second stage method adopts a large current, and the current is gradually increased from 38mA to 48mA in 10 times using the automatic interpolation method; a grid support is added to the bottom of the sample to reduce the temperature gradient and reduce the tendency of Al loss;
[0150] The preheating electron beam scanning line adopts a vertical line that runs through the entire preheating format, and rotates 90° after each scan. The number of preheating scanning lines is 12, and the scanning line spacing is 1mm.
[0151] S5, TiAl alloy printing: within 10ms after the base plate is preheated in S5, the melting beam should be output to melt and print the alloy powder to obtain the TiAl alloy of the required shape, size and accuracy; the melting printing process includes the following steps:
[0152] S51, return time setting: when dividing and slicing the model, the return time of the scan line is set to a fixed value. If a single line is too long, it is re-divided into a combination of several short lines;
[0153] S52, current-speed selection: complete the return time setting in S51, and melt the powder. The melting parameters of different types of powders can be determined by orthogonal test. The following parameters are applicable to TiAl alloy powder: scanning speed is 2.8m / s, scanning current is 5.5mA, line spacing is 0.1mm, and defocus value is 40mA;
[0154] S53, scan line setting: In S52, the melting scan line is spliced by short lines, and rotated 90° after each layer is scanned. In the case of a serious tendency of powder blowing, the dehoff strategy or random strategy can be used instead.
[0155] The microstructure of the TiAl alloy of the desired shape, size and precision in Example S5 was analyzed by scanning electron microscope (SEM-BSE). Figure 6 As shown in the figure, the composition contrast of the molten pool is the same as that of the surrounding area, and the "layering" feature has been completely eliminated; the Al element is evenly distributed in each layer, and there is no obvious contrast difference in the forming direction and the horizontal direction; using X-ray diffraction analysis, D0 19 The values of the contents of the Ti3Al phase of the B2 structure, the β phase of the L10 structure, and the γ phase measured by the half-width method have a maximum difference of 2%.
[0156] In the present embodiment S5, the temperature difference between the top and bottom of the molten pool for any printing parameter combination of the TiAl alloy of the required shape, size and precision is 1200°C, and the temperature of the top of the molten pool is 2200°C.
[0157] In this embodiment, after S5, in the powder recovery stage, the powders that have turned into gray-black and bright white colors should be removed. These powders are generally caused by de-Al or Al plating.
[0158] The TiAl alloy prepared by electron beam selective melting printing in this embodiment is measured on the scale of a molten pool depth, and the maximum difference in Al element content is 0.8at.%.
[0159] The electron beam selective melting printing TiAl alloy to be prepared in this embodiment has a multiphase structure, and there is no "banded structure" caused by de-Al.
[0160] The maximum difference in strength and plasticity between the forming direction and the horizontal direction of the electron beam selective melting printed TiAl alloy to be prepared in this embodiment is 4%, and the strength and plasticity are increased by 30% and 60% respectively compared with the heterogeneous distribution caused by the loss of 1.8at% Al.
[0161] The room temperature properties of the electron beam selective melting printing TiAl alloy to be prepared in this embodiment in the forming direction are as follows: tensile strength is 920 MPa, yield strength is 860 MPa, and elongation is 1.5%.
[0162] Comparative Example 3
[0163] The thickness and composition of the electron beam selective melting printing TiAl alloy prepared in this comparative example are the same as those in Example 3. The preparation method comprises the following steps:
[0164] Steps S1-S3 are the same as those in Example 1;
[0165] S4, bottom plate preheating: preheat the bottom plate in the electron beam selective melting equipment, the preheating temperature of the bottom plate is 950℃, and the powder sintering temperature under the bottom plate is 800℃; the preheating current is 20-48mA and scanned 32 times; no grid support is added to the bottom of the sample;
[0166] Among them, the preheating electron beam scanning line adopts a vertical line that runs through the entire preheating format and rotates 90° after each scan;
[0167] S5, printing of TiAl alloy: After the base plate in S5 is preheated, the melting beam is output to perform melting printing of the alloy powder to obtain the TiAl alloy of the required shape, size and accuracy; during the melting printing process, the melting scanning speed is 3.2m / s, the scanning current is 12mA, and the line spacing is 0.15mm.
[0168] The microstructure of the TiAl alloy of the desired shape, size and precision in this comparative example S5 was analyzed by scanning electron microscope energy spectrum analysis. The microstructure SEM-BSE is as follows: Figure 5 As shown in the figure, there is a clear difference in composition contrast between the molten pool and its surroundings, with a significant "layered" feature.
[0169] In the comparative example S5, the temperature difference between the top and bottom of the molten pool for any combination of printing parameters of the TiAl alloy of the desired shape, size and precision is 1600°C, and the temperature of the top of the molten pool is 2900°C.
[0170] The electron beam selective melting printing TiAl alloy to be prepared in this comparative example was measured on a molten pool depth scale, and the minimum difference in Al element content was 1.4 at.%.
[0171] The difference in strength and plasticity between the forming direction and the horizontal direction of the electron beam selective melting printing TiAl alloy to be prepared in this comparative example is at least 23%.
[0172] The room temperature properties of the electron beam selective melting printing TiAl alloy in the forming direction to suppress the loss of Al element prepared in this comparative example are as follows: tensile strength of 560 MPa, yield strength of 490 MPa, and elongation of 0.5%.
[0173] Example 4
[0174] In this embodiment, the height of the TiAl alloy printed by electron beam selective melting through the Al element loss suppression method is 150 mm, the thickness is 15 mm, and the chemical composition is: Ti45A12Nb2Mn0.8vol.%TiB2 (45XD-TiAl); wherein the Al element loss is 0.26at%.
[0175] A method for suppressing Al element loss in the electron beam selective melting printing TiAl alloy to be prepared in this embodiment includes the following steps:
[0176] S1, smelting: weighing and mixing the TiAl alloy according to the atomic percentage of the electron beam selective melting printing, heating and melting, refining, and casting to obtain an ingot;
[0177] S2. Preparation of alloy powder: The S1 ingot is powdered by a rotating electrode method (PREP), and sieved to a mesh size of 350 to obtain the alloy powder required for electron beam selective melting and printing of TiAl alloy;
[0178] S3, powder spreading: the alloy powder required for S2 is spread in the electron beam selective melting equipment, the powder spreading thickness is 70μm, and the powder spreading thickness is uniform;
[0179] S4, base plate preheating: preheat the base plate in the electron beam selective melting equipment, and keep the vacuum degree of the printing chamber at least 10 -2 mbar, after vacuuming, a small amount of high-purity argon gas was filled in, and the cycle was repeated two to three times; the preheating temperature of the bottom plate was 920℃, and the sintering temperature of the powder under the bottom plate was 900℃; the preheating current adopted a two-stage method, in which a smaller current was used in the first stage method, and the current was gradually increased from 14mA to 36mA in 11 times using the automatic interpolation method; a large current was used in the second stage method, and the current was gradually increased from 38mA to 52mA in 12 times using the automatic interpolation method; a grid support was added to the bottom of the sample to reduce the temperature gradient and alleviate the tendency of Al loss;
[0180] The preheating electron beam scanning line adopts a vertical line that runs through the entire preheating format, and rotates 90° after each scan. The number of preheating scanning lines is 14, and the scanning line spacing is 1mm.
[0181] S5, TiAl alloy printing: within 10ms after the base plate is preheated in S5, the melting beam should be output to melt and print the alloy powder to obtain the TiAl alloy of the required shape, size and accuracy; the melting printing process includes the following steps:
[0182] S51, return time setting: when dividing and slicing the model, the return time of the scan line is set to a fixed value. If a single line is too long, it is re-divided into a combination of several short lines;
[0183] S52, current-speed selection: complete the return time setting in S51, and melt the powder. The melting parameters of different types of powders can be determined by orthogonal test. The following parameters are applicable to TiAl alloy powder: scanning speed is 2.2m / s, scanning current is 6.5mA, line spacing is 0.1mm, and defocus value is 35mA;
[0184] S53, scan line setting: In S52, the melting scan line is spliced by short lines, and rotated 90° after each layer is scanned. In the case of a serious tendency of powder blowing, the dehoff strategy or random strategy can be used instead.
[0185] The microstructure of the TiAl alloy of the desired shape, size and precision in Example S5 was analyzed by scanning electron microscope (SEM-BSE). Figure 8 As shown in the figure, the composition contrast of the molten pool is the same as that of the surrounding area, and the "layering" feature has been completely eliminated; the Al element is evenly distributed in each layer, and there is no obvious contrast difference in the forming direction and the horizontal direction; using X-ray diffraction analysis, D0 19 The values of the Ti3Al phase of the B2 structure, the β phase of the L10 structure and the γ phase of the L10 structure measured by the half-width method have a maximum difference of 3%.
[0186] In the present embodiment S5, the temperature difference between the top and bottom of the molten pool for any combination of printing parameters of the TiAl alloy of the required shape, size and precision is 1700°C, and the temperature of the top of the molten pool is 2900°C.
[0187] In this embodiment, after S5, in the powder recovery stage, the powders that have turned into gray-black and bright white colors should be removed. These powders are generally caused by de-Al or Al plating.
[0188] The TiAl alloy prepared by electron beam selective melting printing in this embodiment is measured on the scale of a molten pool depth, and the maximum difference in Al element content is 1.3at.%.
[0189] The TiAl alloy prepared by electron beam selective melting printing in this embodiment has a multiphase structure, does not have a "banded structure" caused by de-Al, and contains 25% ordered D0 at room temperature. 19 The microstructure contains 5% Ti3Al phase with ordered B2 structure, 7% β phase with ordered B2 structure and 68% γ phase with L10 structure. The number of equiaxed γ grains in the area with 5% equiaxed γ grains is 25% at most compared with the area with 95% lamellar content.
[0190] The maximum difference in strength and plasticity between the forming direction and the horizontal direction of the electron beam selective melting printed TiAl alloy to be prepared in this embodiment is 12%. The strength and plasticity are increased by 35% and 56% respectively compared with the heterogeneous distribution caused by 2at% Al loss.
[0191] The room temperature properties of the electron beam selective melting printing TiAl alloy to be prepared in this embodiment in the forming direction are as follows: tensile strength is 860 MPa, yield strength is 790 MPa, and elongation is 1.4%.
[0192] Comparative Example 4
[0193] The thickness and composition of the electron beam selective melting printing TiAl alloy prepared in this comparative example are the same as those in Example 4. The preparation method comprises the following steps:
[0194] Steps S1-S3 are the same as those in Example 1;
[0195] S4, bottom plate preheating: preheat the bottom plate in the electron beam selective melting equipment, the preheating temperature of the bottom plate is 970℃, and the powder sintering temperature under the bottom plate is 900℃; the preheating current is 28-48mA and scanned 36 times; no grid support is added to the bottom of the sample;
[0196] Among them, the preheating electron beam scanning line adopts a vertical line that runs through the entire preheating format and rotates 90° after each scan;
[0197] S5, printing of TiAl alloy: After the preheating of the base plate in S5 is completed, the melting beam is output to perform melting printing of the alloy powder to obtain the TiAl alloy of the required shape, size and accuracy; during the melting printing process, the melting scanning speed is 2.0m / s, the scanning current is 8.8mA, and the line spacing is 0.12mm.
[0198] The microstructure of the TiAl alloy of the desired shape, size and precision in this comparative example S5 was analyzed by scanning electron microscope energy spectrum analysis. The microstructure SEM-BSE is as follows: Figure 7 As shown in the figure, there is a clear difference in composition contrast between the molten pool and its surroundings, with a significant "layered" feature.
[0199] In this comparative example S5, the temperature difference between the top and bottom of the molten pool for any printing parameter combination of the TiAl alloy of the desired shape, size and precision is 1750°C, and the temperature of the top of the molten pool is 3200°C.
[0200] The electron beam selective melting printing TiAl alloy to be prepared in this comparative example was measured on a molten pool depth scale, and the difference in Al element content was as small as 1.2 at.%.
[0201] The difference in strength and plasticity between the forming direction and the horizontal direction of the electron beam selective melting printing TiAl alloy to be prepared in this comparative example is at least 23%.
[0202] The room temperature properties of the electron beam selective melting printing TiAl alloy in the forming direction to be prepared in this comparative example and to suppress the loss of Al element are as follows: tensile strength is 640 MPa, yield strength is 520 MPa, and elongation is 0.6%.
[0203] Example 5
[0204] In this embodiment, the height of the TiAl alloy printed by electron beam selective melting through the Al element loss suppression method is 190 mm, the thickness is 20 mm, and the chemical composition is calculated by atomic percentage: Al 44.5at%, Nb 4at%, Mo 0.5at%, and the remainder is Ti and unavoidable inclusions; wherein, the Al element loss is 0.3at%.
[0205] A method for suppressing Al element loss in the electron beam selective melting printing TiAl alloy to be prepared in this embodiment includes the following steps:
[0206] S1, smelting: weighing and mixing the TiAl alloy according to the atomic percentage of the electron beam selective melting printing, heating and melting, refining, and casting to obtain an ingot;
[0207] S2. Preparation of alloy powder: The S1 ingot is powdered by a rotating electrode method (PREP), and sieved to a mesh size of 350 to obtain the alloy powder required for electron beam selective melting and printing of TiAl alloy;
[0208] S3, powder spreading: the alloy powder required for S2 is spread in the electron beam selective melting equipment, the powder spreading thickness is 70μm, and the powder spreading thickness is uniform;
[0209] S4, base plate preheating: preheat the base plate in the electron beam selective melting equipment, and keep the vacuum degree of the printing chamber at least 10 -2 mbar, after vacuuming, a small amount of high-purity argon gas is filled in, and the cycle is repeated two to three times; the preheating temperature of the bottom plate is 920℃, and the sintering temperature of the powder under the bottom plate is 890℃; the preheating current adopts a two-stage method. In the two-stage method, a smaller current is used in the first stage method, and the current is gradually increased from 16mA to 38mA in 8 times using the automatic interpolation method; the second stage method adopts a large current, and the current is gradually increased from 40mA to 58mA in 12 times using the automatic interpolation method; a grid support is added to the bottom of the sample to reduce the temperature gradient and reduce the tendency of Al loss;
[0210] The preheating electron beam scanning line adopts a vertical line that runs through the entire preheating format, and rotates 90° after each scan. The number of preheating scanning lines is 14, and the scanning line spacing is 1mm.
[0211] S5, TiAl alloy printing: within 10ms after the base plate is preheated in S5, the melting beam should be output to melt and print the alloy powder to obtain the TiAl alloy of the required shape, size and accuracy; the melting printing process includes the following steps:
[0212] S51, return time setting: when dividing and slicing the model, the return time of the scan line is set to a fixed value. If a single line is too long, it is re-divided into a combination of several short lines;
[0213] S52, current-speed selection: complete the return time setting in S51, and melt the powder. The melting parameters of different types of powders can be determined by orthogonal test. The following parameters are applicable to TiAl alloy powder: scanning speed is 2.2m / s, scanning current is 5.5mA, line spacing is 0.1mm, and defocus value is 35mA;
[0214] S53, scan line setting: In S52, the melting scan line is spliced by short lines, and rotated 90° after each layer is scanned. In the case of a serious tendency of powder blowing, the dehoff strategy or random strategy can be used instead.
[0215] The microstructure of the TiAl alloy of the desired shape, size and precision in Example S5 was analyzed by scanning electron microscope (SEM-BSE). Fig. 9 As shown in the figure, the composition contrast of the molten pool is the same as that of the surrounding area, and the "layering" feature has been completely eliminated; the Al element is evenly distributed in each layer, and there is no obvious contrast difference in the forming direction and the horizontal direction; using X-ray diffraction analysis, D0 19 The values of the contents of the Ti3Al phase of the B2 structure, the β phase of the L10 structure, and the γ phase measured by the half-width method have a maximum difference of 4%.
[0216] The composition content of the TiAl alloy prepared in this embodiment is as follows Fig.11 As shown, the printed composition is close to the preset composition and the Al loss is controllable.
[0217] In the present embodiment S5, the temperature difference between the top and bottom of the molten pool for any combination of printing parameters of the TiAl alloy of the required shape, size and precision is 1100°C, and the temperature of the top of the molten pool is 2000°C.
[0218] In this embodiment, after S5, in the powder recovery stage, the powders that have turned into gray-black and bright white colors should be removed. These powders are generally caused by de-Al or Al plating.
[0219] The TiAl alloy prepared by electron beam selective melting printing in this embodiment is measured on the scale of a molten pool depth, and the maximum difference in Al element content is 0.3at.%.
[0220] The TiAl alloy prepared by electron beam selective melting printing in this embodiment has a multiphase structure, does not have a "banded structure" caused by de-Al, and contains 22% ordered D0 at room temperature. 19 The microstructure contains Ti3Al phase with a structure, 5% volume fraction of β phase with an ordered B2 structure, and 63% volume fraction of γ phase with an L10 structure; the number of equiaxed γ grains in the area with 8% equiaxed γ grains does not exceed 30% compared with the area with 92% lamellar content.
[0221] The maximum difference in strength and plasticity between the forming direction and the horizontal direction of the electron beam selective melting printed TiAl alloy to be prepared in this embodiment is 11%, and the strength and plasticity are increased by 45% and 60% respectively compared with the heterogeneous distribution caused by 2at% Al loss.
[0222] The room temperature properties of the electron beam selective melting printing TiAl alloy to be prepared in this embodiment in the forming direction are as follows: tensile strength is 940 MPa, yield strength is 900 MPa, and elongation is 1.6%.
[0223] Example 6
[0224] In this embodiment, the height of the TiAl alloy printed by electron beam selective melting through the Al element loss suppression method is 260 mm, the thickness is 30 mm, and the chemical composition is calculated by atomic percentage: Al 44.5at%, Nb 4at%, Mo 0.5at%, and the balance is Ti and unavoidable inclusions; wherein, the Al element loss is 0.28at%.
[0225] A method for suppressing Al element loss in the electron beam selective melting printing TiAl alloy to be prepared in this embodiment includes the following steps:
[0226] S1, smelting: weighing and mixing the TiAl alloy according to the atomic percentage of the electron beam selective melting printing, heating and melting, refining, and casting to obtain an ingot;
[0227] S2. Preparation of alloy powder: The S1 ingot is powdered by a rotating electrode method (PREP), and sieved to a mesh size of 350 to obtain the alloy powder required for electron beam selective melting and printing of TiAl alloy;
[0228] S3, powder spreading: the alloy powder required for S2 is spread in the electron beam selective melting equipment, the powder spreading thickness is 100μm, and the powder spreading thickness is uniform;
[0229] S4, base plate preheating: preheat the base plate in the electron beam selective melting equipment, and keep the vacuum degree of the printing chamber at least 10 -2 mbar, after vacuuming, a small amount of high-purity argon gas is filled in, and the cycle is two to three times; the preheating temperature of the bottom plate is 900℃, and the sintering temperature of the powder under the bottom plate is 900℃; the preheating current adopts a two-stage method. In the two-stage method, a smaller current is used in the first stage method, and the current is gradually increased from 18mA to 40mA in 10 times using the automatic interpolation method; the second stage method adopts a large current, and the current is gradually increased from 40mA to 58mA in 12 times using the automatic interpolation method; a grid support is added to the bottom of the sample to reduce the temperature gradient and reduce the tendency of Al loss;
[0230] The preheating electron beam scanning line adopts a vertical line that runs through the entire preheating format, and rotates 90° after each scan. The number of preheating scanning lines is 14, and the scanning line spacing is 1mm.
[0231] S5, TiAl alloy printing: within 10ms after the base plate is preheated in S5, the melting beam should be output to melt and print the alloy powder to obtain the TiAl alloy of the required shape, size and accuracy; the melting printing process includes the following steps:
[0232] S51, return time setting: when dividing and slicing the model, the return time of the scan line is set to a fixed value. If a single line is too long, it is re-divided into a combination of several short lines;
[0233] S52, current-speed selection: complete the return time setting in S51, and melt the powder. The melting parameters of different types of powders can be determined by orthogonal test. The following parameters are applicable to TiAl alloy powder: scanning speed is 2.8m / s, scanning current is 5.5mA, line spacing is 0.1mm, and defocus value is 40mA;
[0234] S53, scan line setting: In S52, the melting scan line is spliced by short lines, and rotated 90° after each layer is scanned. In the case of a serious tendency of powder blowing, the dehoff strategy or random strategy can be used instead.
[0235] The microstructure of the TiAl alloy of the desired shape, size and precision in Example S5 was analyzed by scanning electron microscope (SEM-BSE). Fig.10 As shown in the figure, the composition contrast of the molten pool is the same as that of the surrounding area, and the "layering" feature has been completely eliminated; the Al element is evenly distributed in each layer, and there is no obvious contrast difference in the forming direction and the horizontal direction; using X-ray diffraction analysis, D0 19 The values of the Ti3Al phase of the B2 structure, the β phase of the L10 structure and the γ phase of the L10 structure measured by the half-width method have a maximum difference of 3%.
[0236] The composition content of the TiAl alloy prepared in this embodiment is as follows Fig.12 As shown, the printed composition is close to the preset composition and the Al loss is controllable.
[0237] In the present embodiment S5, the temperature difference between the top and bottom of the molten pool for any combination of printing parameters of the TiAl alloy of the required shape, size and precision is 1300°C, and the temperature of the top of the molten pool is 2100°C.
[0238] In this embodiment, after S5, in the powder recovery stage, the powders that have turned into gray-black and bright white colors should be removed. These powders are generally caused by de-Al or Al plating.
[0239] The TiAl alloy prepared by electron beam selective melting printing in this embodiment is measured on the scale of a molten pool depth, and the maximum difference in Al element content is 0.7at.%.
[0240] The TiAl alloy prepared by electron beam selective melting printing in this embodiment has a multiphase structure, does not have a "banded structure" caused by de-Al, and contains 26% ordered D0 at room temperature. 19 The microstructure consists of a Ti3Al phase with a structure, a β phase with an ordered B2 structure at a volume fraction of 9%, and a γ phase with an L10 structure at a volume fraction of 6%. The number of equiaxed γ grains in the area with 6% of equiaxed γ grains does not exceed 30% compared with the area with 94% of lamellar content.
[0241] The maximum difference in strength and plasticity between the forming direction and the horizontal direction of the electron beam selective melting printed TiAl alloy to be prepared in this embodiment is 7%, and the strength and plasticity are increased by 24% and 31% respectively compared with the heterogeneous distribution caused by 2at% Al loss.
[0242] The room temperature properties of the electron beam selective melting printing TiAl alloy to be prepared in this embodiment in the forming direction are as follows: tensile strength is 870 MPa, yield strength is 800 MPa, and elongation is 1.6%.
[0243] Example 7
[0244] In this embodiment, the height of the TiAl alloy printed by electron beam selective melting is 300 mm and the thickness is 20 mm. The chemical composition is calculated by atomic percentage: Al 44.5at%, Nb 4at%, Mo 0.5at%, and the balance is Ti and unavoidable inclusions; wherein, the Al element loss is 0.22at%.
[0245] A method for suppressing Al element loss in the electron beam selective melting printing TiAl alloy to be prepared in this embodiment includes the following steps:
[0246] S1, smelting: weighing and mixing the TiAl alloy according to the atomic percentage of the electron beam selective melting printing, heating and melting, refining, and casting to obtain an ingot;
[0247] S2. Preparation of alloy powder: The S1 ingot is powdered by a rotating electrode method (PREP), and sieved to a mesh size of 350 to obtain the alloy powder required for electron beam selective melting and printing of TiAl alloy;
[0248] S3, powder spreading: the alloy powder required for S2 is spread in the electron beam selective melting equipment, the powder spreading thickness is 50μm, and the powder spreading thickness is uniform;
[0249] S4, base plate preheating: preheat the base plate in the electron beam selective melting equipment, and keep the vacuum degree of the printing chamber at least 10 -2 mbar, after vacuuming, a small amount of high-purity argon gas is filled in, and the cycle is repeated two to three times; the preheating temperature of the bottom plate is 910℃, and the sintering temperature of the powder under the bottom plate is 870℃; the preheating current adopts a two-stage method. In the two-stage method, a smaller current is used in the first stage method, and the current is gradually increased from 18mA to 38mA in 8 times using the automatic interpolation method; the second stage method adopts a large current, and the current is gradually increased from 40mA to 58mA in 10 times using the automatic interpolation method; a grid support is added to the bottom of the sample to reduce the temperature gradient and reduce the tendency of Al loss;
[0250] The preheating electron beam scanning line adopts a vertical line that runs through the entire preheating format, and rotates 90° after each scan. The number of preheating scanning lines is 10, and the scanning line spacing is 1mm.
[0251] S5, TiAl alloy printing: within 10ms after the base plate is preheated in S5, the melting beam should be output to melt and print the alloy powder to obtain the TiAl alloy of the required shape, size and accuracy; the melting printing process includes the following steps:
[0252] S51, return time setting: when dividing and slicing the model, the return time of the scan line is set to a fixed value. If a single line is too long, it is re-divided into a combination of several short lines;
[0253] S52, current-speed selection: in S51, the return time setting is completed, and the powder is melted. The melting parameters of different types of powders can be determined by orthogonal test. The following parameters are applicable to TiAl alloy powder: scanning speed is 2.4m / s, scanning current is 4.5mA, line spacing is 0.1mm, and defocus value is 35mA;
[0254] S53, scan line setting: In S52, the melting scan line is spliced by short lines, and rotated 90° after each layer is scanned. In the case of a serious tendency of powder blowing, the dehoff strategy or random strategy can be used instead.
[0255] The microstructure of the TiAl alloy of the required shape, size and precision in Example S5 is analyzed by energy spectrum analysis using a scanning electron microscope, and the printed microstructure composition curve is as follows: Fig.13 As shown, the printed composition is close to the preset composition, and the Al loss is controllable. 12 points are evenly taken on the entire sample, and the composition is as follows Fig.14As shown in the figure, the Al element is evenly distributed on the entire forming surface. Specifically, the composition contrast between the molten pool and the surrounding area is the same, and the "layering" feature has been completely eliminated; and the Al element is evenly distributed in each layer, and there is no obvious contrast difference in the forming direction and the horizontal direction; using X-ray diffraction analysis, D0 19 The values of the Ti3Al phase of the B2 structure, the β phase of the L10 structure and the γ phase of the L10 structure measured by the half-width method have a maximum difference of 3%.
[0256] In the present embodiment S5, the temperature difference between the top and bottom of the molten pool for any combination of printing parameters of the TiAl alloy of the required shape, size and precision is 1000°C, and the temperature of the top of the molten pool is 1900°C.
[0257] In this embodiment, after S5, in the powder recovery stage, the powders that have turned into gray-black and bright white colors should be removed. These powders are generally caused by de-Al or Al plating.
[0258] The TiAl alloy prepared by electron beam selective melting printing in this embodiment is measured on the scale of a molten pool depth, and the maximum difference in Al element content is 0.4at.%.
[0259] The TiAl alloy prepared by electron beam selective melting printing in this embodiment has a multiphase structure, does not have a "banded structure" caused by de-Al, and contains 29% ordered D0 at room temperature. 19 The microstructure contains Ti3Al phase with a structure, 5% volume fraction of β phase with an ordered B2 structure, and 66% volume fraction of γ phase with an L10 structure; the number of equiaxed γ grains in the area with 5% equiaxed γ grains does not exceed 30% compared with the area with 95% lamellar content.
[0260] The maximum difference in strength and plasticity between the forming direction and the horizontal direction of the electron beam selective melting printed TiAl alloy to be prepared in this embodiment is 12%. The strength and plasticity are increased by 46% and 72% respectively compared with the heterogeneous distribution caused by 2% Al loss.
[0261] The room temperature properties of the electron beam selective melting printing TiAl alloy to be prepared in this embodiment in the forming direction are as follows: tensile strength is 980 MPa, yield strength is 900 MPa, and elongation is 1.3%.
[0262] The above scheme, the present invention proposes an electron beam selective melting printing TiAl alloy and a preparation method that suppresses the loss of Al element, which can solve many technical problems existing in the existing electron beam printing TiAl alloy process, thereby reducing production costs and improving economic benefits.
[0263] The present invention optimizes the phase change path and the temperature range of the single-phase region of the alloy through reasonable composition adjustment, and effectively controls the loss of Al element in the printing process by controlling factors such as base plate preheating, current and speed, scanning line setting in the preheating stage and return time, current and speed, scanning line setting in the melting stage.
[0264] The present invention obtains a higher printing process window through the optimization design of printing parameters, which is beneficial to controlling the loss process of Al element during the printing process; a TiAl alloy with no stratification and the difference in Al element distribution between the upper and lower parts of the molten pool is not more than 0.5at.%, and the difference in strength and plasticity between the forming direction and the horizontal direction is not more than 10% is printed.
[0265] The preparation method of the present invention completely eliminates the "banded structure" stratification phenomenon in TiAl alloy through parameter optimization design, can reduce the temperature difference between powder and molten pool, and obtain fine full-lamellar structure with uniform elements and grains. This structure has good high-temperature performance and proposes a new concept for blade materials and processing.
[0266] The preparation method of the present invention can be widely used for printing TiAl alloys such as TNM, 4822, high Nb-TiAl, 45XD, etc., and can achieve the suppression of aluminum element loss, and has strong alloy process adaptability; in particular, the design parameter domain in the preparation method is controllable, and there is no need to add additional equipment or links. The process is simple, the cycle is short, the cost is low, and the efficiency is high.
[0267] In summary, compared with other traditional methods, the method of the present invention can print TiAl alloy products with high shape design freedom and high dimensional accuracy by selecting components and controlling the preheating stage and the melting stage; it can synergistically improve the room temperature and high temperature mechanical properties, inhibit the loss of Al elements, has high resource utilization, short process, high efficiency, and is conducive to large-scale industrial production and promotion.
[0268] It should be understood that the term "and / or" in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship, but it may also indicate an "and / or" relationship. Please refer to the context for specific understanding.
[0269] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, at least one of a, b, or c can mean: a, b, c, ab, ac, bc, or abc, where a, b, and c can be single or multiple.
[0270] It should be understood that in various embodiments of the present invention, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.
[0271] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. An electron beam selective melting printing TiAl alloy, characterized in that: The electron beam selective melting printing TiAl alloy for suppressing Al element loss has a height of 15-300 mm, a thickness of 15-50 mm, and a chemical composition in atomic percentage of: Al 40-50 at%, Nb 2-10 at%, Mo 0-0.9 at%, Cr 0-2.5 at%, Si 0-2 at%, C 0-0.5 at%, and the remainder is Ti and unavoidable inclusions; wherein, the Al element loss is 0.2-0.35 at%.
2. The electron beam selective melting printing TiAl alloy according to claim 1, characterized in that: The electron beam selective melting printing TiAl alloy is measured on the scale of a molten pool depth, and the difference in Al element content should not be greater than 0.5at.%.
3. The electron beam selective melting printing TiAl alloy according to claim 1, characterized in that: The TiAl alloy printed by electron beam selective melting has a multiphase structure, does not have a "banded structure" caused by de-Al, and contains 20-30% ordered D0 at room temperature. 19 The microstructure contains Ti3Al phase with ordered B2 structure, β phase with ordered B2 structure with volume fraction ≤10%, and γ phase with L10 structure with volume fraction 60-70%. The number of equiaxed γ grains in the area with 5-10% equiaxed γ grains does not exceed 30% compared with the area with lamellar content of 90-95%.
4. The electron beam selective melting printing TiAl alloy according to claim 1, characterized in that: The difference in strength and plasticity between the forming direction and the horizontal direction of the electron beam selective melting printed TiAl alloy that suppresses Al element loss is no more than 10%, and the strength and plasticity are respectively increased by 20-50% compared with the heterogeneous distribution caused by Al loss of 1-3at%.
5. A method for suppressing Al element loss in electron beam selective melting printing of TiAl alloy according to claim 1, characterized in that: The method for suppressing Al element loss in electron beam selective melting printing of TiAl alloy comprises the following steps: S1, smelting: weighing and mixing the TiAl alloy according to the atomic percentage of the electron beam selective melting printing, heating and melting, refining, and casting to obtain an ingot; S2. Preparation of alloy powder: The S1 ingot is powdered by a rotating electrode method or gas atomization, and sieved to obtain the alloy powder required for electron beam selective melting and printing of TiAl alloy; S3, powder spreading: the alloy powder required for S2 is spread in the electron beam selective melting equipment, and the powder spreading thickness is uniform; S4, bottom plate preheating: preheat the bottom plate in the electron beam selective melting equipment, the preheating current adopts a two-stage method, and a grid support is added to the bottom of the sample; S5. Printing of TiAl alloy: After the S4 base plate is preheated, the alloy powder is melted and printed to obtain a TiAl alloy of the desired shape, size and precision.
6. The method for suppressing Al element loss in electron beam selective melting printing of TiAl alloy according to claim 5, characterized in that: The mesh size of the sieve in S2 is 350 mesh, and the thickness of the powder in S3 is 40-120 μm.
7. The method for suppressing Al element loss in electron beam selective melting printing of TiAl alloy according to claim 5, characterized in that: The preheating temperature of the bottom plate in S4 is 900-950℃, and the sintering temperature of the powder under the bottom plate is 850-900℃; in the two-stage method, the first stage method uses a smaller current, and gradually increases from 10mA to 40mA using the automatic interpolation method for 5-10 times; the second stage method uses a large current, and gradually increases from 40mA to 60mA using the automatic interpolation method for 5-10 times.
8. The method for suppressing Al element loss in electron beam selective melting printing of TiAl alloy according to claim 5, characterized in that: The electron beam scanning line for preheating in S4 adopts a vertical line that runs through the entire preheating format, and rotates 90° after each scan. The number of branch lines of the preheating scanning line is 10-16, and the scanning line spacing is 0.2-1mm.
9. The method for suppressing Al element loss in electron beam selective melting printing of TiAl alloy according to claim 5, characterized in that: In S4, the melting beam should be output within 10ms after the base plate is preheated to melt and print the alloy powder; the melting printing process of S5 includes the following steps: S51, return time setting: when dividing and slicing the model, the return time of the scan line is set to a fixed value. If a single line is too long, it is re-divided into a combination of several short lines; S52, current-speed selection: complete the return time setting in S51, and melt the powder. The melting parameters of different types of powders can be determined by orthogonal test. The following parameters are applicable to TiAl alloy powder: when the powder layer thickness is 40-70μm, the scanning speed is 1.8-2.8m / s, the scanning current is 3-6mA, the line spacing is 0.05-0.2mm, and the defocus value is 20-30mA; when the powder layer thickness is 70-120μm, the scanning speed is 2.0-4.8m / s, the scanning current is 4-9mA, the line spacing is 0.05-0.2mm, and the defocus value is 30-60mA; S53, scan line setting: In S52, the melting scan line is spliced by short lines, and rotated 90° after each layer is scanned. In the case of a serious tendency of powder blowing, the dehoff strategy or random strategy can be used instead.
10. The method for suppressing Al element loss in electron beam selective melting printing of TiAl alloy according to claim 5, characterized in that: The microstructure of the TiAl alloy with the required shape, size and precision in S5 was analyzed by the energy spectrum analysis of the scanning electron microscope. The Al element in the energy spectrum scanning diagram is evenly distributed in each layer, and there is no obvious contrast difference in the forming direction and the horizontal direction. Using X-ray diffraction analysis, D0 19 The difference in the contents of Ti3Al phase of B2 structure, β phase of B2 structure and γ phase of L10 structure measured by the half-width method should not be greater than 5%.
Citation Information
Patent Citations
Ti-Al alloy component preparing method based on electron beam 3D printing technology
CN107695350A
Powder metallurgy titanium-aluminum-based composite material and preparation method thereof
CN109694971A
Preparation method of low-cost titanium hydrogen storage alloy and product thereof
CN117070773A
High-strength TiAl alloy with nearly full lamellar structure and preparation method of high-strength TiAl alloy
CN117753991A
Electron beam selective melting TiAl alloy and preparation method
CN118513565A
Cited By
Layered regulation and control method for microstructure of additive manufacturing titanium-aluminum alloy
CN120060689A
